Study of Student Success Indicators based on the Viewpoints of the Students of Mazandaran University of Medical Sciences - Afkhaminia, Farzaneh; Siamian, Hasan; Behnampour, Naser; Moghimi, Adib; Karimpour, Shiva (Acta informatica medica, 2018)
One of the performance measures of any educational system is the degree to which students learn their education. Academic achievement includes the acquisition of a set of skills and abilities that are acquired during the course and in decision making and the various issues of leadership of individuals. A variety of factors affect the academic success of students. The present study aims to investigate the successful student's point of view from students of Mazandaran University of Medical Sciences in 2016-2017. This cross-sectional study was conducted with an analytical approach. 595 students from all faculties of Mazandaran University of Medical Sciences and Health Services who were studying in the second semester of 2016-2017. To collect data, a researcher-made questionnaire made 144 questions, "Student Success Index" with 18 areas of reading, writing, speaking skills, listening skills, learning styles, memory, reading skills, critical thinking skills, motivation, self-esteem, personal relationships, conflict resolution, health, time management, Financial Management, Personal Purposes, Work Planning and Support Resources, each of which includes 8 fields. The Mann-Whitney U test and Kruskal-Wallis test used for analysis. There is a meaningful relationship between auditory skills, reading, creative thinking and critique, motivation, personal relationships, conflict resolution, time management, personal goals, work planning, sources of support and School. )P<0.05(. Also, there is a significant relationship between the dimension of personal goals and educational level (P <0.05). In terms of personal dimensions, PhD students had lower levels than the average. Empowering human resources through education is possible. Obviously, with the increase in the efficiency of universities and higher education institutions, one can take a major step in the development of the country. It is suggested that in order to improve the quality of these skills among students, the teaching strategies for learning these skills should be included in the student's curriculum, or by conducting workshops on the use of these strategies during the study period for students for improving and developing it.